Medication-Related Osteonecrosis of the Jaw: a Brief Review, Treatment and Practical Guidelines for Dentists - Albu-Stan, Ioana-Aurița; Albu, Daniel-Emil; Cerghizan, Diana; Eremie, Lia Yero; Jánosi, Kinga; Baloș, Monica; Copotoiu, Constantin (Journal of Interdisciplinary Medicine, 2017)
Osteonecrosis of the jaws is a complication after treatment with antiresorptive drugs. Bisphosphonates (BPs) are widely used to treat conditions with bone metastases of malignant tumors such as multiple myeloma, breast cancer, prostatic cancer, as well as hypercalcemia of malignancy, osteoporosis, Paget’s disease, and osteogenesis imperfecta. Denosumab is an antiresorptive agent that is used for the treatment of osteoporosis or metastatic bone diseases. These antiresorptive agents improve the quality of life of patients by increasing strength and bone mineral density, and reducing the risk of bone fractures. More than a decade had passed since the first publication of this pathology, and the occurrence of the disease, its pathophysiology, and proper treatment methods are still not fully elucidated. Prevention is critical in medication-related osteonecrosis of the jaw, because the treatment is difficult, and there are no universally accepted treatment protocols. There is an accepted approach of palliation of symptoms and controlling the associated infections. Treatment may follow one of three procedures: conservative management of pain, conservative or extensive (segmental) surgery, depending on the disease stage.